Manajemen Peningkatan Kualitas Guru Di Pondok Pesantren Hujjaturrahmah Tanjung Pura - Intan Sari, Muamar Al Qadri, Mhd. Fuad Zaini Siregar (Pusdikra Publishing, 2023)
Teacher at Hujjaturrahman Islamic Boarding School Tanjung Pura. Field research was used to obtain the data needed in this study, namely by using data collection tools through observation, interviews or structured interviews, and documentation. The data obtained was then processed and analyzed. In this study, qualitative research was used with an analytical description approach, namely by describing the research results obtained through structured interviews on research sources. The results of the qualification program research, in this program the teachers at the Hujjaturrahmah Tanjung Pura Islamic Boarding School already have the qualifications required by the government, which means that in this case it has shown that the teachers at the Hujjaturrahmah Tanjung Pura Islamic Boarding School have good competence, and there are still some teachers who teach not in accordance with qualifications possessed. Furthermore, the certification program, in this case is the same as the qualification program where in the certification program there are several teachers who have not taken part in certification. The efforts of the madrasa head for this program are always carried out and the waka always provides assistance in the form of services. In the training program, madrasas dispatch educators when they receive training invitations. Not only training outside the madrasah, but also carrying out training within the madrasah. The implementation is also in accordance with existing steps, starting from identifying the problems faced by teachers to following up on training activities. The teacher quality improvement program is research, in this research program carried out by the head of the madrasa in the form of classroom action research so that the research leads to supervision . Although there are several teachers who carry out classroom action research, there is no implementation yet.